PENERAPAN MEDIA GAMBAR BERSERI BERBASIS AI UNTUK MENINGKATKAN KETERAMPILAN MENULIS CERITA FANTASI PADA SISWA KELAS VII SMPN 7 MADIUN SEMESTER GANJIL TAHUN PELAJARAN 2026/2027 - Zhafira, Nabila Zahra; Kuncoro Hadi , Panji; Budiharto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of fantasy story writing skills among Grade VII students at SMP 7 Madiun is evidenced by their difficulties in generating ideas, developing plotlines, and translating their imagination into written form.This study aims to describe the implementation of Artificial Intelligence (AI)-based sequential image media and to analyze the improvement in 7th-grade students' fantasy story writing skills resulting from the use of this media. The study employs the Kemmis and McTaggart Classroom Action Research (CAR) model, conducted over two cycles. Each cycle comprises the stages of planning, action implementation, observation, and reflection. The research subjects consisted of 30 7th-grade students. Data collection involved observation, testing, and documentation, while data analysis was conducted using both qualitative and quantitative methods. The results indicate that the implementation of AI-based sequential image media successfully improved students' fantasy story writing skills. This is demonstrated by the rise in the class average score from 68.07 in the pre-cycle stage to 77.33 in Cycle I and 85.47 in Cycle II. The percentage of students achieving mastery also increased from 33.33% in the pre-cycle stage to 63.33% in Cycle I, reaching 93.33% in Cycle II. The findings suggest that AI-based sequential image media is an effective instructional tool for helping students generate ideas, structure plotlines, and enhance their creativity in writing fantasy stories.